Constitutionalism and the Rule of Law in Indonesia: Historical Development and Contemporary Issues - Irman Putra; Arief Fahmi Lubis (Westscience Press, 2023)
This paper explores the historical development and contemporary issues of constitutionalism and the rule of law in Indonesia through juridical analysis and literature review. The study traces the evolution of Indonesian law from the colonial period, through the ratification of the 1945 Constitution, the Guided Democracy and New Order regimes, and the Reformation era. It highlights key milestones and challenges in building a strong constitutional democracy. Contemporary issues such as judicial independence, human rights, and governance are analysed to understand ongoing efforts and obstacles in strengthening the rule of law in Indonesia. By synthesising existing literature and legal texts, this paper provides a comprehensive overview of Indonesia's legal trajectory and current challenges, and offers insights into future reforms needed to enhance constitutional governance.